2015
DOI: 10.1016/j.fuproc.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclohexane as hydrogen-donor in ultradispersed catalytic upgrading of heavy oil

Abstract: The incorporation of catalysts to enhance downhole upgrading in the Toe-to-Heel Air Injection (THAI) process is limited by deactivation due to coking arising from the cracking of heavy oil. This study aims to reduce the catalyst deactivation problems that can occur with upgrading of heavy oils. Ultradispersed catalyst particles could potentially replace pelleted catalysts which may be difficult to regenerate once deactivated during the THAI operation. The dispersed particles could potentially be applied once t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…The pressure inside the reactor was controlled by back pressure regulator (Swagelok, Manchester, UK), through the regulation of gas holdup inside the reactor. The ratio of H-donor solvent to oil used was 0.045 (g/g), which is within the range of the optimum reported by Hart et al [22]. The addition of the H-donor solvent caused negligible impact on the API gravity of the THAI feed oil, while the resultant effect on viscosity due to thinning was less than a 10% decrease.…”
Section: Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…The pressure inside the reactor was controlled by back pressure regulator (Swagelok, Manchester, UK), through the regulation of gas holdup inside the reactor. The ratio of H-donor solvent to oil used was 0.045 (g/g), which is within the range of the optimum reported by Hart et al [22]. The addition of the H-donor solvent caused negligible impact on the API gravity of the THAI feed oil, while the resultant effect on viscosity due to thinning was less than a 10% decrease.…”
Section: Methodssupporting
confidence: 73%
“…The risk associated with hydrogen gas has shifted attention to hydrogen carriers such as polycyclic organic compounds, which are known to store, transport and liberate hydrogen in a safer and cost-effective means [21]. Moreover, it is well-known that asphaltene is soluble in aromatic solvents, so the presence of polycyclic organic solvent in the catalytic upgrading medium would keep the asphaltene solubilized, while undergoing cracking into smaller fragments which are readily hydrogenated by the liberated hydrogen [22]. On the other hand, the injection of steam has been reported as an alternative technique to supply hydrogen in situ through the water-gas shift (WGS) reaction and can also help to suppress coke formation [10,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coke formation can be suppressed when the catalytic upgrading is carried out under a hydrogen rich environment [15]. The difficulty, safety and cost associated with transporting hydrogen gas itself into the reservoir have shifted attention to hydrogen-donor solvents such as polycyclic compounds (i.e., cyclohexane, decalin and tetralin) [16]. These organic liquids potentially store and transport hydrogen in a safer and less challenging manner when compared to external transport of hydrogen gas itself into the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The dehydrogenation of tetralin to naphthalene can be used as a hydrogen source to promote in situ hydrocracking and hydrogenation reactions in the catalytic addon (CAPRI) to THAI. Hart et al [16] reported that the use of cyclohexane as hydrogen-donor solvent for downhole catalytic upgrading of heavy oil suppressed coke formation. Many studies have reported the use of tetralin as H-donor solvent [14,17,18], and the findings showed that coke formation is suppressed and upgraded oil quality improved.…”
Section: Introductionmentioning
confidence: 99%